2021
DOI: 10.1021/acscatal.1c00714
|View full text |Cite
|
Sign up to set email alerts
|

Iridium(III)-Catalyzed Branch-Selective C–H Alkenylation of Aniline Derivatives with Alkenes

Abstract: The branch-selective C−H alkenylation with alkenes using an iridium catalyst is reported. The Ir(III)-catalyzed reaction of aniline derivatives that contain a pyrimidine-directing group with vinylsilanes and terminal aliphatic alkenes results in branch-selective C−H alkenylation. The reaction provides a broad substrate scope for aniline derivatives, and a variety of functional groups are tolerated. Density functional theory calculations were performed in an attempt to understand the origin of the branch select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…This trend is in agreement with experimental results that indicate that a branched product is preferably obtained. The origin of this rare branch selectivity arises from the steric repulsion between the TMS group and the equatorial acetic acid ligand on the nonparticipating rhodium atom (Figure A) . In the linear-selective migratory insertion TSs, the TMS group is closer to the methyl group of the acetic acid ligand, which forces the ligand to adopt a distorted form compared to the preferred linear coordination.…”
Section: Resultsmentioning
confidence: 99%
“…This trend is in agreement with experimental results that indicate that a branched product is preferably obtained. The origin of this rare branch selectivity arises from the steric repulsion between the TMS group and the equatorial acetic acid ligand on the nonparticipating rhodium atom (Figure A) . In the linear-selective migratory insertion TSs, the TMS group is closer to the methyl group of the acetic acid ligand, which forces the ligand to adopt a distorted form compared to the preferred linear coordination.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported a branch-selective C−H alkenylation of anilines with vinylsilanes using [Cp*IrCl 2 ] 2 as a catalyst that involved the regioselective migratory insertion of a vinylsilane into a C−Ir bond and is governed by the strain energy resulting from steric repulsion between a silyl group and the Cp* ligand. 20 Taking advantage of this protocol, we found that the Rh(III)-catalyzed C−H activation/alkene cyclization of aniline derivatives with vinylsilanes provides highly regioselective C3-substituted indo-…”
Section: ■ Introductionmentioning
confidence: 95%
“…The optimal conditions combine [Cp*IrCl 2 ] 2 (5 mol %) as a catalyst, AgSbF 6 (20 mol %) as an additive, and a stoichiometric amount of Ag 2 CO 3 as an oxidant in 1,2‐dichloroethane as a solvent at 80 °C for 4 h under a nitrogen atmosphere (Scheme 35). [40] A wide range of differently substituted anilines ( 61 ) possessing electron‐withdrawing as well as electron‐donating substituents were all smoothly coupled with vinyl silanes, providing the alkenylated product in good to moderate yields. In the case of meta ‐substituted anilines, the alkenylation exclusively occurred at the less hindered position.…”
Section: Aromatic C(sp2)‐h Alkenylationmentioning
confidence: 99%
“…In the proposed mechanism, the reaction initiated from the coordination of ( 61 g ) to the Ir(III) complex followed by the ortho C−H bond activation generates the metallacycle intermediate ( E5 ) (Scheme 36). [40] The metallacycle intermediate (E5 ) also directly formed from the [Cp*IrCl 2 ] 2 under the catalytic condition. Then, coordination of alkene with metallacycle intermediate ( F5) and subsequent insertion between the Ir−C bond produces the eight‐membered metallacycle ( G5 ).…”
Section: Aromatic C(sp2)‐h Alkenylationmentioning
confidence: 99%